CHANGES IN SOME PHYSICAL PROPERTIES OF SOIL AMENDED WITH EFFLUENT OF EMAMI PAPER MILLS LOCATED AT BALGOPALPUR, BALASORE, ORISSA - S. C. PRADHAN; PRASHANTI BEHERA (The Bioscan, 2011)
Paper mill effluent has been amended to the soil in laboratory conditions. Physical properties like bulk density, porosity and water holding capacity of the soil changed with respect to the concentration of the effluent. With increase in concentration of the effluent, a significant decrease in the bulk density was observed. There was an increase in porosity of amended soil with increase in the amount of effluent. The water holding capacity of the soil also increased with increase in the concentration of the effluent. So far as the days of exposures are concerned no significant difference in the bulk density, porosity and water holding capacity of the amended soil was observed.